(untitled) (Research, Society and Development, 2020)
Introduction: Among the agricultural products, soybeans (Glycine max) possui elevated expansão, occupying a prominent position, peel high produtibilidade e for being easy to grow. As a crescent increase in Saudi foods, soy vem ganhando espaço no markets com a elaboración de novos produtos such as: farinhas de soy, sucos enriched with soy, queijos, iogurte de soy, soy leite, extract hydrossolúveis and textured proteins. Objective: To assess or profile the consumer in relation to soybeans and their derivatives. Methods: This is a quantitative study, of a descriptive nature, carried out in Caxias-MA, not 100 participants were interviewed, of both sexes, and different age groups, randomly in locality such as: supermarkets, public market, praças and faculties, through a questionnaire about soy intake and its derivatives. Discussion and Results: A textured soy protein and soy "leite" foram os more produtos conhecidos and consumed hair interviewed, two maioria respondents reported 65% no conhecer os benefits. Conclusion: The base was not small or habit and freqência e consumption of soybeans and their derivatives pela população estuda, mesmo or Brazil being two major world producers do grão. Isso is due so much to lack of information about the benefits of two products, how much lack of costume of popular consumption or as part of the usual food.